Virtual Classroom Competences Required by Electrical Installation and Maintenance Works Trade Teachers in Technical Colleges in Yobe State, Nigeria - Fwah, Karnilius Gideon; Idowu, Adebayo John; Dasofunjo, Abiodun (Darul Yasin Al Sys, 2024)
This study investigated the virtual classroom proficiencies needed by Electrical Installation and Maintenance Works trade teachers in Technical Colleges in Yobe State, Nigeria. Employing a descriptive survey research design, the population of the study was 69 individuals, comprising 53 teachers and 16 ICT experts from eight Technical Colleges in Yobe State, Nigeria. Due to the manageable size of the population, the entire population was included in the study, eliminating the need for sampling. Data collection utilized the